Peran Efektif Pondok Pesantren Al- Qurtuby dalam Pembentukan Karakter Santri - Atania Zahro; Mochammad Syafiuddin Shobirin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the effective role of the Al-Qurtuby Islamic Boarding School in shaping the character of students. As one of the oldest Islamic educational institutions in Indonesia, the Islamic boarding school holds a very strategic position in developing the morals and ethics of the younger generation, especially amidst the increasing moral crisis that is occurring in the modern era. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation so as to be able to describe the reality of the character formation of students in depth. The results show that the Al-Qurtuby Islamic Boarding School has three main functions: as a transmission of Islamic knowledge, a preserver of Islamic traditions, and a center for the development of prospective ulama (Islamic scholars). These three functions contribute significantly to fostering a character of peace, tolerance, independence, and a sense of responsibility in students. The character formation process is carried out through various methods, including the exemplary behavior of kyai (Islamic clerics) and ustaz (Islamic teachers), habituation in daily activities, and the provision of educational advice and sanctions. Supporting factors for the formation of students' character at this boarding school include the students' high internal motivation to learn, maintained discipline, and a conducive Islamic boarding school environment full of religious values. However, this study also identified inhibiting factors, such as student boredom due to busy schedules, limited facilities, and the challenge of adapting to changing times that demand innovation in teaching methods. The implications of this research are that it provides information for Islamic boarding school administrators in designing more effective strategies for developing character education, while also serving as a reference for other Islamic educational institutions wishing to adopt a similar approach. Thus, Islamic boarding schools remain relevant in producing a generation with noble character capable of facing future social and moral challenges.